The plaza in the hispanic andean cities of Peru - Orellana Tapia, Máximo (2022)
The plaza in the hispanic andean cities of Peru The process of Spanish implantation in Andean territory during the 16th century began in the nascent mestizo cities with their plazas, due to their symbolic character and because they facilitated the concentration of population, functionality and monuments. The study documents and compares typological characteristics of the urban morphology of six early Hispanic-Andean urban centers: Cajamarca, Jauja, Cuzco, Ayacucho, Huancavelica and Puno from a historiographic perspective. The information obtained allows understanding situational qualitative aspects still visible in singular spatialities that even when originated in past foundational acts of the viceroyalty, have had continuity in later scenarios of longed republican Independence that today sustain and manifest validity.